Peranan Mekanisme Corporate Governance, Corporate Social Responsibility, dan Female Commissioners pada Financial Performance - Setiawan, Yan Christianto (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p01, 2023)
There are several factors that can affect a company's financial performance, such as corporate social responsibility (CSR) and corporate governance. This study aims to examine the effect of social responsibility and corporate governance on financial performance. The research population is all sectors of business entities registered on the IDX and issuing sustainability reports for the 2018-2020 period. The number of research samples is 123 company observations. The research used a purposive sampling technique in taking the sample. The researcher uses a random effect model on the panel data structure for hypothesis testing analysis. The results showed that the performance of CSR, independent board members, and the proportion of female board members had a positive effect on financial performance, while the size of the board of commissioners had no effect on financial performance. Research contributes mainly to the development of regulations, to increase the obligation to implement CSR and to raise the standard for the proportion of independent members and women on the board of commissioners. Keywords: Performance; CSR; CG; Gender.